Promotion of Food and Nutritional Security and Food Sovereignty in Family Production Units in the Canton of Siquirres, Province of Limón, Costa Rica - Aguirre Rosales, Diego (2021)
The project was developed in Siquirres, a canton of the Limón province. The process consisted of training, learning by doing, and the dialogue of knowledge systems to promote the production of twenty-five food security and nutrition crops to promote food sovereignty in the production units of thirty-four families and a school in the marginal rural territory of the mentioned canton. The process included the participation of two organizations of producers, public institutions, the National University, and advanced students of the Agronomy career of the School of Agricultural Sciences of the National University.